Effect of entomopathogenic fungi over development stages of Bemisia tabaci (Hemiptera: Aleyrodidae) - ESPINEL-C., CARLOS; TORRES-T., LISSETTE; COTES-P., ALBAMARINA (Revista Colombiana de Entomología, 2009)
Bemisia tabaci is a worldwide economically important insect pest. Entomopathogenic fungi represent a promising option for its control. However, to achieve their effective use under field conditions it is necessary to generate knowledge about the most susceptible development stages to control and the better strategies of biopesticide application. The objective of the present work was to determine the individual and combined effect of two preformulations based on Beauveria bassiana (Balsamo) Vuillemin and Isaria fumosorosea Wize (Ifr) (=Paecilomyces fumosoroseus), as compared with a biopesticide based on Lecanicillium lecanii, (Zimmermann) (Ascomycota: Hypocreales), on development stages of B. tabaci, under laboratory conditions. Bean plants (Phaseolus vulgaris L.) were infested with adults of the insect and each product at 1x107  conidia/mL-1  was sprayed on egg, first, second, third and fourth nymphal instars. At 14 days postaplication, efficiency percentage on individual and combined application was estimated. Efficiency of the combined application was evaluated by applying fungi on second instar. First and second instars were the most susceptible to three microorganisms, with efficiency of 60 and 78.3%, respectively. I. fumosorosea caused higher efficiency on egg stage (40%). No significant differences were obtained between individual and combined application of the products, in both cases an efficiency upper to 60% was obtained. Second instar was the most susceptible and individual application of the microorganisms was selected to evaluate in field bioassays.